STUDI KELIMPAHAN MEROPLANKTON KEPITING Scylla sp. PADA KONDISI LINGKUNGAN PERAIRAN YANG BERBEDA DI WILAYAH BARAT PESISIR KOTA TARAKAN - Sinta Triana; Dhimas Wiharyanto (Jurnal Harpodon Borneo, 2016)
One type of biota in the mangrove waters ecosystem that is crabs meroplankton. Condition of in this stage is very important for crabs abundance in the mangrove ecosystem. This study aims to determine the abundance crabs meroplankton and water quality conditions west part in the waters surrounding the Mangrove Conservation Area and Bekantan (KKMB), Beringin, SDF Harbour, and Mamburungan Estuary during high tide occurs. Sampling of crab meroplankton conducted at four using plankton net. The result showed that the crabs meroplankton are commonly found in zoea and megalopa stage. Generally, condition of crab meroplankton abundance in the part western of the Tarakan city obtained more abundant during in the evening than the afternoon. The highest abundance during the affternoon get at Estuary Mamburungan about 7 ind, while in the evening found at KKMB about 108 ind. Water quality conditions in the waters research found that salinity in the afternoon 23 to 33 g/l, pH 6.6 to 7.2, temperature 29-33°C, and DO 3.05-5.50 mg/l. While at night the salinity value is the range of 25-33 g/l, pH 6.6 to 7.9, temperature 23-31°C, and DO from 3.17 to 5.90 mg/l. Keywords : Abundance, Crabs meroplankton, Mangrove, Water Quality.